Parallel machines scheduling with fuzzy simulated annealing - Santos, A. S. (2014)
Scheduling problems occurring in parallel machines manufacturing environments are quite usual and many different methods have been applied for solving it. These methods vary from the application of more or less simple heuristics and rules up to more complex methods, including distinct kind of metaheuristics. In this paper we discuss a fuzzy optimization method using simulated annealing (Fuzzy-SA) for solving an unrelated parallel machines manufacturing scheduling problem. To demonstrate the potential of our method we use an illustrative example of a parallel machines scheduling (PMS) problem and then we analyse it and perform statistical tests with 20 instances.